5-Benzoyl-4-hydroxy-6-(4-nitrophenyl)-4-trifluoromethyl-3,4,5,6-tetrahydropyrimidin-2(1H)-one monohydrate - Yang, Feng-Ling (International Union of Crystallography, 2008)
The asymmetric unit of the title compound, C(18)H(14)F(3)N(3)O(5)·H(2)O, contains two independent formula units. The two heterocyclic molecules differ in the orientations of the benzoylphenyl group with respect to the tetrahydropyrimidine ring [C—C—C—C torsion angles of 64.5 (3) and 67.1 (3)°]. In both molecules the pyrimidine ring adopts a half-chair conformation. The molecules are linked into a two-dimensional network parallel to (001) by N—H⋯O and O—H⋯O hydrogen bonds.